Biostimulant Effects of Glutacetine® and Its Derived Formulations Mixed With N Fertilizer on Post-heading N Uptake and Remobilization, Seed Yield, and Grain Quality in Winter Wheat - Maignan, Victor; Bernay, Benoit; Géliot, Patrick; Avice, Jean-Christophe (Frontiers in Plant Science, 2020)
Biostimulants could play an important role in agriculture particularly for increasing N fertilizer use efficiency which is essential for maintaining both yield and grain quality in bread wheat, which is a major global crop. In the present study, we examined the effects of mixing urea-ammonium-nitrate fertilizer (UAN) or urea with 5 new biostimulants containing Glutacetine® or its derivative formulations (VNT1, 2, 3 and 4) on the physiological responses, agronomic traits and grain quality of winter wheat. A first experiment under greenhouse conditions showed that VNT1, VNT3 and VNT4 significantly increased the seed yield and grain numbers per ear. VNT4 also enhanced total plant nitrogen (N) and total grain N, which induced a higher N Harvest Index (NHI). The higher post-heading N uptake (for VNT1 and VNT4) and the acceleration of senescence speed with all formulations enabled better nutrient remobilization efficiency, especially in terms of N mobilization from roots and straw towards the grain with VNT4. The grain ionome was changed by the formulations with the bioavailability of iron improved with addition of VNT4, and the phytate concentrations in flour were reduced by VNT1 and VNT4. A second experiment in 3 contrasting field trials confirmed that VNT4 increased seed yield and N Use Efficiency. Our investigation reveals the important role of these new formulations in achieving significant increases in seed yield and grain quality.